Dharma and Rules of Dvija in the 2nd Adhyaya of the Manusmṛti - Dulyasucharit, Thawatchai (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย)
Manusmṛti or Mānavadharmaśāstra is an important Sanskrit scripture of ancient India, comprises of dharmas and rules for brāhmaṇas and general citizen, It is probably composed around 200 before CE or the 2nd Century. The text relates conversations of Manu and Ṛṣi Bhṛgu. Manusmṛti has several important aspects, espectially social orders, heritage and quarrels. It’s not only used in the ancient times, but also used in later times in some countries in South East Asia, such as Mon, and Thai, as appeared in their legal texts of the similar titles. The composition of the text is verses. The metre used is called Anustubh (Śloka), consiting of 4 padas or quarter-verses of eight syllables, totalling 2,694 verses and separated into 12 chapters (adhyāya). The main contents of Manusmṛti can be divided into 8 parts: Creation of the world, Source of dharma, duties of the four castes, four steps of life, laws and judgment, means of removing sins, quarrells and judgement, cycles of life, attending Brahman. The 2nd chapter’s content is dharma and rules for Barhmacarin, comprising of 249 verses. This cane be divided into 31 parts. In this article, the translator translated the 2nd chapter of Manusmriti from Sanskrit into Thai, keeping the scripture’s styles of language for the readers who want to study the style of the texts. The translator does hope that the readers of the Thai translation could have academic benefits in aspects of dharma, Hindu rites, and Sanskrit, as well.